BIOLOGICAL EVALUATION OF SCHIFF BASES OF NEW ISATIN DERIVATIVES FOR ANTI ALZHEIMER'S ACTIVITY - Mohan.P, Chandra; Rao. J, Venkateshwar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Isatin can be used for synthesis of many heterocyclic compounds having diverse pharmacological activities. Several Isatin derivatives are being developed as promising drugs in the area of central nervous system diseases. In the present study, six novel Isatin derivatives, especially Schiff bases were screened for possible Anti-Alzheimer's activity using the scopolamine model with. Acute oral toxicity, along with in vivo and invitro tests like Radial arm maze (RAM), Morris water maze (MWM), Jumping box test along with assessment of Lipid peroxidation (LPO), Super oxide dismutase (SOD), Catalase and Acetyl choline esterase levels followed by histopathological study of rat brain tissues. Various Schiff bases of Isatin derivatives showed significant anti-amnesic activity as assessed by behavioural test using RAM, MWM and Jumping box test. There was a significant increase (p < 0.05) in brain LPO levels in animals treated with scopolamine when compared to scopolamine and Isatin group. There was a significant decrease (p < 0.05) in brain SOD, catalase activity in animals treated with scopolamine when compared to scopolamine and Isatin group. Also, the animals treated with Isatin and scopolamine showed a significantly decreased acetyl cholinesterase activity when compared to scopolamine treated groups. The histopathological study also revealed less amyloid formation in groups treated with Isatin derivatives when compared to control group. The anti amnesic effects of Isatin derivatives demonstrated in the present study may be due to anti-oxidant action. Considering the results of behavioural, biochemical and histopathological studies, we hypothesize that Schiff bases of Isatin derivatives may act directly as a free radical scavenger or regulator to inhibit AChE, oxidative activity and ionic homeostasis imbalance in neurons induced by scopolamine. Key words: Anti-Alzheimer's activity, Schiff bases, Isatin